The Impact of Social Policies on Self-Reliance Incentives for Roma in Central and Eastern Europe - Milcher, Susanne; Zigová, Katarína (Ekonomika, 2005)
In this paper, we review the social systems in five European countries: Bulgaria, the Czech Republic, Hungary, Slovakia and Romania. We focus here on regulations towards households with insufficient income. Based on this, we analyse the impact of social transfers on self-reliance incentives of the Roma minority in particular, using data from the UNDP/ILO survey conducted in 2001 in the five countries.